From karma to sin: a kaleidoscopic theory of mind and Christian experience in northern Thailand. (25th March 2020) - Aulino, Felicity
Abstract: In this essay, I argue for a 'kaleidoscopic' theory of mind implicit in people's common‐sense awareness of themselves, others, and reality in northern Thailand. Phenomenal experience is here generally understood as contingent on a host of factors, from personal habits to the influence of others, such that sensory perceptions themselves are in part a consequence of prior action (karma) with moral import. When Thai people convert to Christianity, they reject karma in favour of a God who will absolve a believer of all offence. Drawing on both neo‐Pentecostal and Buddhist Thais' rich descriptions of their encounters with the divine and a host of other 'supernatural' experiences, I show how many Thai Christians maintain an abridged sense of karmic contingency. With attention to local theory of mind, non‐monotheistic knowledge formations come into focus, highlighting the unique nature of the individualism emerging among Thai congregants and the stakes such individuation has for them. Abstrait: Du karma au péché : une théorie kaléidoscopique de l'esprit et du vécu des chrétiens dans le nord de la Thaïlande Résumé Dans cet essai, l'autrice avance des arguments en faveur d'une théorie « kaléidoscopique » de l'esprit, implicite dans la conscience ordinaire de soi, des autres et de la réalité, dans le nord de la Thaïlande. Dans cette région, l'expérience phénoménologique est généralement comprise comme liée à de multiples facteurs, habitudes personnelles aussi bien qu'influences des autres, de sorte que les perceptions sensorielles à proprement parler sont en partie la conséquence d'actions antérieures ( karma ) ayant un retentissement moral. Lorsqu'ils se convertissent au christianisme, les Thaïs réfutent l'idée du karma pour se tourner vers un Dieu qui absoudra les croyants de tout péché. À partir des riches descriptions faites par des Thaïs, néopentecôtistes aussi bien que bouddhistes, de leur rencontre avec le divin et de nombreuses autres expériences « surnaturelles », l'article montre comment les thaïs chrétiens gardent souvent la notion, certes tronquée, de la contingence karmique. La théorie locale de l'esprit intègre des régimes de connaissance non monothéistes, mettant en lumière la nature unique de l'individualisme qui émerge parmi les fidèles thaïs et les enjeux qu'implique pour eux cette individuation.